Anti-inflammatory activities of Cleome gynandra Linn. and Melicope ptelefolia champ. ex Benth. for possible use in a topical cream formulation - Ismail, Muhammad Aiman Haiqal (2021)
Herbal formulation is defined as the formulation of one or more than two herbs, with documented efficacies in treating inflammatory diseases, including skin conditions. Cleome gynandra (Maman), and Melicope ptelefolia (Tenggek Burung) are traditional herb in Malaysia that well-known as a vegetable dish. Both C. gynandra and M. ptelefolia leaves in methanolic extract have been proven for their anti-inflammatory properties. Previous data on these two herbs were mainly reported their efficacy in the form of standardized extract, while limited data on their anti-inflammatory activity as herbal formulation, particularly as cream-based products. These studies aimed to investigate the anti-inflammatory activities of C. gynandra, M. ptelefolia and their cream formulation by using in vitro and in vivo models. The single herb extract of C. gynandra, M. ptelefolia and their herbal formulation were tested for their toxicity testing using MTT assay and anti-inflammatory activities by nitric oxide inhibition assay. The results indicated that single herb C. gynandra exhibited the highest percentage of cell viability (110.59%) at concentration 4 mg/mL on RAW 264.7 cells compared to M. ptelefolia (38.01%), suggesting that C. gynandra extract is less cytotoxic compared to M. ptelefolia. Among the herbal formulations, the highest percentage of cell viability (92.59%) at concentration 4 mg/mL on RAW 264.7 cells were shown in the formulation that contains the highest concentration of C. gynandra (C. gynandra: M. ptelefolia at ratio 70:30 (w/w)). For nitric oxide inhibition assay, single herb C. gynandra exerted comparable (P>0.05) anti-inflammatory activities with diclofenac sodium drug (0.6μM) at 0.5-2 mg/mL. In the meantime, the herbal formulations of C. gynandra: M. ptelefolia at ratios 30:70, 50:50, and 70:30, respectively, were insignificant, suggesting that all samples have equal efficacies (P>0.05). From the result in vitro assay, extract with best activities overall (single herb C. gynandra) were then further developed into topical anti-inflammatory cream. Subsequently, C. gynandra in a cream formulation was tested on arachidonic acidinduced ear oedema model of male Sprague-Dawley rats. C. gynandra cream treated rats showed significantly (P<0.05) higher percentage recovery (70.21%) than the negative control (27.43%) and basal cream (55.8%), indicating that this C. gynandra cream was effectively reducing inflammation symptoms in the ear oedema model in rats. C. gynandra cream also caused no irritation and no changes to the haematological and histopathological parameters in the skin irritation model in rats, suggesting its nontoxic activity for 28 days of exposure. In conclusion, C. gynandra could be potential as a herbal formulation in cream-based for treating skin related inflammatory conditions.